Bond life degradation of steel strand and concrete under combined corrosion and fatigue. (October 2017) - Li, Fumin; Qu, Yaxu; Wang, Jianghao
Abstract: The destruction of the bond between steel bar and concrete induced by corrosion–fatigue damage is important in concrete-structure research, but related works are few. This study aimed to investigate the corrosion–fatigue damage behavior of the bond in pre-tensioning prestressed concrete structures. We conducted a series of combined actions of corrosion and fatigue (i.e., three levels of corrosion and eight levels of fatigue) chronically for 20 bond specimens of steel strand and concrete. Results showed that the corrosion–fatigue failure of the bond occurred mainly in split mode. The corrosion–fatigue life of the bond decreased with increased fatigue stress range under a constant action of corrosion. Similarly, the corrosion–fatigue life of the bond decreased with increased corrosion current density under constant fatigue action. An empirical model of the corrosion–fatigue bond life was established by regressing and extending the experimental results. From the model, the correlation equation of corrosion and fatigue for the constant life of two million was derived. Highlights: A combined action of corrosion and fatigue was simulated for bond degradation. Bond corrosion–fatigue damage behavior of steel strand and concrete was obtained. The bond corrosion–fatigue life model of steel strand and concrete was built.